Bibliometric analysis of targeted immunotherapy for osteosarcoma-current knowledge, hotspots and future perspectives - Hu, Yunxiang; Yang, Rui; Ni, Shuai; Song, Zefeng (Frontiers in Immunology, 2025)
ObjectiveThe objective of this study is to conduct a bibliometric analysis on examining the current condition, areas of interest, and rising trends of immunotherapy for osteosarcoma (ITFOS), as well as its importance in associated research domains.MethodsAn extensive collection of academic papers on the use of ITFOS was obtained from the Web of Science between January 1, 2000 and October 20, 2023. Then, using a variety of tools like HisCite, VOSviewer, CiteSpace, and the bibliometrix package, a bibliometric study was carried out. This study included the collection of information on country, institution, author, journal, and keywords.ResultsA comprehensive analysis was undertaken on a total of 616 publications obtained from 247 journals, encompassing the contributions of 3725 authors affiliated with 831 institutes spanning across 43 countries/regions. Notably, China exhibited the highest quantity of published 277 (44.99%) articles on ITFOS. The most productive institution was Zhejiang University, with 26 (4.22%) publications. The author with the highest publication output was Tsukahara, Tomohide from Japan with 15 (2.44%) publications. The article with the most citation was “DOI: 10.1200/JCO.2014.58.0225”. Frontiers in Immunology demonstrated the highest level of productivity, having published a total of 31 (5.03%) articles. The most frequently used were “osteosarcoma,” “immunotherapy,” and “cancer,”. Meanwhile, “sequencing”, “prognostic signature” and “immune microenvironment“ have been identified as the research frontiers for the forthcoming years.ConclusionThis paper provides a thorough evaluation of current research trends and advancements in ITFOS. It includes relevant research findings and emphasizes collaborative efforts among authors, institutions, and countries.